Desain Bangunan Bagi Numbak dan Ngerirun pada Sistem Distribusi Air Irigasi Subak Berdasarkan Konsep Pemias - Sumiasih, Ni Kadek; Tika, i Wayan; Budisanjaya, Putu Gede (Jurnal BETA (Biosistem dan Teknik Pertanian); Vol 4 No 2 (2016): September, 2016)
Divider structure (tembuku) numbak and ngerirun is one of structure that used as divider in Subak water irrigation. Diversion of flow in the tembuku ngerirun was causing reduction that influenced by the difference speed and makes the difference rate of flow with tembuku numbak . The purposes of this research were: (1) to determine the level of the pemias coefficient on tembuku numbak and ngerirun , and (2) to calculate the dimensions of the tembuku numbak and ngerirun that review by pemias aspects. The real rate of flow analysed by measuring the width and height of water on the tembuku and the must rate of flow calculated by using the ratio of irrigated land area. The real rate of flow and the must rate of flow were used to determine pemias coefficients and pemias coefficients used to determine the must width of the threshold design of tembuku . Based on analysis, the average pemias coefficient was 0.095 or a value of pemias reduction was 0.095. Correlation of height of water and pemias coefficient was very high with R 2 was 0.942. RMSE of width threshold value was 38.86%. The must width of the threshold at Subak is obtained by dividing the real width threshold with (1- pemias coefficients). After socialized to some pekaseh , they were mostly agree if there pemias coefficients that can be used to give pelampias on tembuku ngerirun .
Keywords: Divider stucture (tembuku), numbak and ngerirun, Rate of flow, Pemias coefficient,width threshold,Subak